Das escolas isoladas ao Grupo Escolar : a instrução pública primária em Mariana - MG (1889-1915) - Vieira, Lívia Carolina (Universidade Federal de São Carlos, 2011)
This dissertation is inserted in the area of foundations of Education of the Program of Post- Graduation in Education of the Federal University of São Carlos. A study of the field of History of School institutions, which has the object of study Mariana-MG Primary School (a public and primary school). The period chosen has beginning in 1889, to monitor the first initiatives of the government republican of the city in relation to primary public education, and extends until the year 1915- year in which José Ignácio has left the direction of the Group and moved to Ituiutaba-MG. The motivation for the installation of the Group, teachers, students and curricula were observed. Show how was the public education and primary schools in the municipality in the period before the creation of the Group, in calls Isolated Schools, was also a concern of the dissertation. For such was been consulted different archives: Archive Public Miner, Archive of the Municipal Council of Mariana, Acquis of the State School Dom Benevides and newspapers. Tried to relation the particular context The School Group of Mariana- a wider context of the state scenario and, in some moments, nationally. The conclusions pointed to the fact that education carried out in the Group School of Mariana was elitist. It studied mainly the children of declared "republicans" with good financial conditions, while in isolated schools were the poorest and residents of districts and parishes of the city. The quality and the structure of the place of teaching were much better in the Group. The results allow the beginning of a construction of the history of the same, bringing together various documents, which may assist other researchers interested in studying the primary education in the period of the First Republic, and even the School Group of Marian and/or the isolated schools that still has much to be studied.
Keywords: Educação - história; Grupo Escolar; Programa de ensino - escolas isoladas; Brasil - história - república velha, 1889-1930; Primeira República; First Republic; Primary School; Isolates Schools; CIENCIAS HUMANAS::EDUCACAO